A Literature-based Approaches on Multicultural Education - Aydin, Hasan (KAMLA-RAJ ENTERPRISES, 2013)
Multicultural education has developed over the last several decades and it is becoming increasingly recognized as a significant educational issue and it is an approach to teaching and learning that is based on democratic values and beliefs and affirms cultural pluralism within culturally diversesocieties. The purpose of this piece to bring conceptual clarity to the field by examining what multicultural education means. With regard to those issues, this study could help educators clarify and reflect upon current understandings of multicultural education and ideas of appropriate practices. This paper presents a comprehensive research on multicultural education which has been written and it also evaluates the literature for its contributions to both the theory and the practice of multicultural education.
Keywords: Multicultural Education; Curriculum; Practice; Review of Literature; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics